2022
DOI: 10.1590/1414-431x2022e11831
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of linalool against fluconazole-resistant clinical strains of vulvovaginal Candida albicans and its predictive mechanism of action

Abstract: Candida albicans is the most frequently isolated opportunistic pathogen in the female genital tract, with 92.3% of cases in Brazil associated with vulvovaginal candidiasis (VVC). Linalool is a monoterpene compound from plants of the genera Cinnamomum , Coriandrum, Lavandula , and Citrus that has demonstrated a fungicidal effect on strains of Candida spp., but its mechanism of action is still unknown. For this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 40 publications
1
5
0
1
Order By: Relevance
“…Linalool oxide : This is a monoterpene acyclic tertiary alcohol that has been described as having antifungal activity against the fungus plant pathogen Guignardia camelliae [ 65 ], Candida albicans [ 66 ], and Trichophyton rubrum [ 67 ]. It has a lot of applications as a vitamin E precursor, in cosmetics, and in detergents, being the most widely used terpene in the food industry because of its fragrant and flavor properties [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Linalool oxide : This is a monoterpene acyclic tertiary alcohol that has been described as having antifungal activity against the fungus plant pathogen Guignardia camelliae [ 65 ], Candida albicans [ 66 ], and Trichophyton rubrum [ 67 ]. It has a lot of applications as a vitamin E precursor, in cosmetics, and in detergents, being the most widely used terpene in the food industry because of its fragrant and flavor properties [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies of antifungal activity of linalool against the resistant strains of C. albicans have shown good correlation between experimental and theoretical studies performed by molecular docking. It was found that linalool probably causes damage of the C. albicans cell wall and plasma membrane, what can be explained by its interaction with three important enzymes involved in their biosynthesis, including lanosterol 14-α-demethylase [ 41 ]. Other molecular docking studies performed for 60 plant-origin compounds revealed that 48 of them have shown binding affinity with lanosterol 14-α-demethylase [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…(JALAGAS ME, et al, 2006) Apesar da eficácia comprovada de todos os antifúngicos descritos, a preocupação com a resistência à cepa considera novas alternativas ao tratamento, no Rio Grande do Sul um estudo constatou a resistência in vitro de 42% dos isolados resistente ao fluconazol oral, enquanto outro em Santa Catarina encontrou 100% de resistência ao mesmo fármaco (BRANDOLT, 2017). A mais recente possível inovação farmacológica encontrada foi acerca do linalol, uma molécula fungicida que afeta a integridade da membrana e da parede celular de C. albicans, porém mais pesquisas devem ser realizadas (MEDEIROS, 2022).…”
Section: Discussionunclassified